VCO making training: Improving coconut economics and village existence in Pananjung - Irma Dwi Saputri; Nadila Rifatul Karimah; Tatang Permana (Dedicated: Journal of Community Services (Pengabdian kepada Masyarakat), 2024)
Coconut farming in Pananjung Village, Pangandaran, faces economic challenges due to the low market value of coconuts. To address this, the article proposes a training initiative for Virgin Coconut Oil (VCO) production, targeting PKK members. VCO, extracted at temperatures below 60°C, retains nutritional value and offers economic advantages. The training aims to empower women in the community to produce high-quality VCO efficiently. Through a descriptive research approach, the article discusses the economic potential of VCO, emphasizing its health benefits and market demand. The proposed training not only enhances VCO production skills but also contributes to the overall economic development of Pananjung Village by optimizing local resources. The successful implementation of the training is evident in the increased skills of the participants, the economic upliftment of coconut farmers, and the utilization of VCO as a valuable product. In conclusion, the training proves instrumental in improving the economic viability of coconut farming in Pananjung Village and contributes to the overall well-being and sustainability of the community.   Abstrak Pertanian kelapa di Desa Pananjung, Pangandaran, menghadapi tantangan ekonomi akibat nilai pasar kelapa yang rendah. Untuk mengatasi hal ini, artikel ini mengusulkan inisiatif pelatihan produksi Virgin Coconut Oil (VCO), dengan target anggota PKK. VCO, diekstraksi pada suhu di bawah 60°C, mempertahankan nilai gizi dan menawarkan keuntungan ekonomi. Pelatihan bertujuan memberdayakan perempuan di komunitas untuk menghasilkan VCO berkualitas tinggi secara efisien. Melalui pendekatan penelitian deskriptif, artikel membahas potensi ekonomi VCO, menekankan manfaat kesehatannya dan permintaan pasar. Pelatihan yang diusulkan tidak hanya meningkatkan keterampilan produksi VCO tetapi juga berkontribusi pada pengembangan ekonomi keseluruhan Desa Pananjung dengan mengoptimalkan sumber daya lokal. Keberhasilan pelaksanaan pelatihan terlihat dari peningkatan keterampilan peserta, peningkatan ekonomi petani kelapa, dan pemanfaatan VCO sebagai produk bernilai. Secara keseluruhan, pelatihan terbukti menjadi instrumen penting dalam meningkatkan viabilitas ekonomi pertanian kelapa di Desa Pananjung serta berkontribusi pada kesejahteraan dan keberlanjutan komunitas. Kata Kunci: Buah kelapa; KKN tematik; VCO; virgin coconut oil